PEMBINGKAIAN PEMBERITAAN APARTEMEN CIKARANG DI â€œXYZ.COMâ€ DAN â€œABCD.COMâ€ - Ine Anggraini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
Project development is undertaken by Lippo Group currently has licensing issues such as Environmental Impact Analysis and Building Permit. This turned out to be an agenda deemed important by the mass media to be known by the public. What is in the mass media will affect the subjective reality of social interaction. This study aims to examine the coverage of XYZ.com and ABCD.com in presenting news about the construction of apartments in Cikarang namely